Cognitive outcome in late preterm babies - Ayu Setyorini; Soetjiningsih Soetjiningsih; Ekawaty L. Haksari (Paediatrica Indonesiana, 2010)
Background Late preterm babies are at risk for delayed cognitive outcome, but little attention has been paid on this issue. There has been a general assumption that this group of babies will have the same development as full-term babies.Objective To compare the cognitive development between late preterm babies and full-term babies.Methods A prospective cohort study was conducted at the Department of Child Health Medical School of Udayana University/Sanglah Hospital. Babies with 34 to 42 weeks of gestational age who were born in Sanglah Hospital between November 1st 2007 and December 31st 2008, were recruited to the study. Cognitive development of each baby was measured by Mullen Scale’s of Early Learning twice, at 7 days and 3 months of age. We used corrected age for late preterm babies and chronological age for fullterm babies.Results The incidence of under-average development for late preterm babies at three months corrected age was 47.8% compared to 4.1% among fullterm babies (P < 0.0001). The relative risk for under-average development among late preterm babies was 11.8 (95%CI 9.95 to 13.75). Multivariate analysis revealed late preterm influenced cognitive significantly with OR 17.01 (95%CI 1.15 to 32.87).Conclusions Cognitive outcome of late preterm babies was delayed compared to full-term babies.